Trace elements in graphite and graphite-bearing marbles from Central and East Rhodopes, Bulgaria; Review of the Bulgarian Geological Society; Vol. 86, Pt 2 - Yossifova M. Mariana; Dimitrova D. Dimitrina; Arbuzov S. I. Sergei Iwanowitsch; Tacheva E. Elena; Sergeeva I. Ivanina (2025, 2025)
Title screen